ASSISTANCE FOR THE DEVELOPMENT OF ACADEMIC TEXT AND RAPERDASUS SUSTAINABLE DEVELOPMENT IN WEST PAPUA PROVINCE: Peraturan - D. Mandacan, Nataniel; Bawole, Roni; Warami, Hugo; Rahayu, Muji (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The empirical problem in assisting the preparation of Academic Papers and the Draft of Special Regional Regulations for the Province of West Papua is that there is no synchronization between previous and current legislation regarding sustainable development. Specifically, in West Papua Province, sustainable development is based on the view that natural resources have a limited capacity to accept the impact of human activities. The objectives of this mentoring activity are (1) to develop a framework for academic texts as the main umbrella for the draft of special regional regulations; (2) to draft a special regional regulation on Sustainable Development in the Province of West Papua; (3) evaluate the implementation of Perdasus No. 10 of 2019 concerning Sustainable Development in West Papua Province; and (4) propose new articles (inserts) as a form of an amendment to the existing special regional regulations. The output of this strengthening activity is expected to contribute to harmonizing, regulating, limiting, considering, and covering the scope of special regional regulations related to Sustainable Development in West Papua Province. Participants in the mentoring activity consisted of (1) Provincial Government Elements, (2) Universities, (3) Customary Institutions, (4) Technical Regional Apparatus Organizations, and (5) Members of the DPR and MRP West Papua, totaling 75 people. This mentoring activity resulted in: (1) changes to the provisions of Articles I and II norms, and (2) Insertions of Articles 5, 6A, 26A, and 49A.